The Efforts of Imam Ibn Ya'ish in Interpretation in his Book Sharh al-Mufassal - Surah al-Fatihah as a Model - Saleh Ibrahim Hussein, (Islamic Sciences Journal, 2025)
ABSTRACT There is no disagreement that the language of every nation carries the meanings and connotations of that language, and the Arabic language contains meanings and connotations that constitute a miracle in itself, but it became the language of the Glorious Quran, and the language of the most eloquent speaker of Arabic throughout the ages, the illiterate Prophet, our master Muhammad, may Allah bless him and grant him peace. When the Glorious Quran came with rules, meanings and connotations, the Arabic language was the bearer of them and the container for them. What the one who is familiar with the meanings and connotations of the Glorious Quran needs most is the clarification of the Arabic language in clarifying and explaining those meanings and connotations. It is not possible to reach the intended meaning of the verses of the Glorious Quran without being familiar with the sciences of the Arabic language, at the top of which is the science of grammar, as it is a law that clarifies and defines what the minds stray from and the feet slip. The grammarians had the most prominent impact in clarifying the meanings and connotations of the verses of the Glorious Quran, at the top of them the great Imam Ibn Ya’ish - may Allah Almighty have mercy on him - in his wonderful and enjoyable book (Sharh al-Mufassal); except that his efforts were scattered throughout his book as they appeared in the discussions of grammar from the beginning of the book to the end. This research was a step towards shedding light on his efforts in interpreting the Glorious Quran and explaining its meanings.